The Impact of the Principal's Authoritarian Leadership on the Discipline and Compliance of Educators and Education Personnel - Nurti, Nurti; Muhammad, Muhammad; Agus, Agus (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to describe the influence of authoritarian leadership of school/madrasah principals on the discipline and compliance of educators and education personnel in the school environment. This type of research is qualitative research Library research. The research results show that the authoritarian leadership style implemented by the principal significantly influences the level of discipline among educators and education staff. Educators and education staff tend to exhibit high levels of discipline due to strict supervision and clear punishments. However, this compliance is temporary, driven more by fear and pressure than by personal awareness and responsibility. Furthermore, an authoritarian leadership style also lowers work motivation, inhibits creativity, and reduces active participation in school decision-making. Thus, it can be concluded that authoritarian leadership by principals is indeed capable of improving formal discipline, but is less effective in fostering compliance stemming from intrinsic awareness and harmonious working relationships. This study recommends that principals adopt a more participatory and communicative leadership style to create a healthy and productive work climate.